The Roles of White Adipose Tissue and Liver NADPH in Dietary Restriction-Induced Longevity - Leah E. Jamerson; Patrick C. Bradshaw (MDPI AG, 2024)
Dietary restriction (DR) protocols frequently employ intermittent fasting. Following a period of fasting, meal consumption increases lipogenic gene expression, including that of NADPH-generating enzymes that fuel lipogenesis in white adipose tissue (WAT) through the induction of transcriptional regulators SREBP-1c and CHREBP. SREBP-1c knockout mice, unlike controls, did not show an extended lifespan on the DR diet. WAT cytoplasmic NADPH is generated by both malic enzyme 1 (ME1) and the pentose phosphate pathway (PPP), while liver cytoplasmic NADPH is primarily synthesized by folate cycle enzymes provided one-carbon units through serine catabolism. During the daily fasting period of the DR diet, fatty acids are released from WAT and are transported to peripheral tissues, where they are used for beta-oxidation and for phospholipid and lipid droplet synthesis, where monounsaturated fatty acids (MUFAs) may activate Nrf1 and inhibit ferroptosis to promote longevity. Decreased WAT NADPH from PPP gene knockout stimulated the browning of WAT and protected from a high-fat diet, while high levels of NADPH-generating enzymes in WAT and macrophages are linked to obesity. But oscillations in WAT [NADPH]/[NADP+] from feeding and fasting cycles may play an important role in maintaining metabolic plasticity to drive longevity. Studies measuring the WAT malate/pyruvate as a proxy for the cytoplasmic [NADPH]/[NADP+], as well as studies using fluorescent biosensors expressed in the WAT of animal models to monitor the changes in cytoplasmic [NADPH]/[NADP+], are needed during ad libitum and DR diets to determine the changes that are associated with longevity.